Development of the 'History Quest' History Learning Media Based on Google Lens to Improve Learning Outcomes of Grade X Students at SMA: Pengembangan Media Pembelajaran Sejarah "History Quest” Berbasis Google Lens Untuk Meningkatkan Hasil Belajar Siswa Kelas X di SMA - Satrio Wibowo; M. Faris Abdil Aziz; diana rohmawati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to develop History Quest, a history learning media based on Google Lens, to enhance the learning outcomes of Grade X students at SMA. The research employed the Research and Development (R&D) approach with the ADDIE model, consisting of Analyze, Design, Development, Implementation, and Evaluation stages. The media was designed as an interactive card game integrating QR codes linked to historical video content accessed via Google Lens, combined with a Guided Inquiry Learning approach to foster active and collaborative learning. The product was validated by material and media experts and tested in classroom implementation. The results indicate an improvement in students’ learning outcomes, with the average score increasing from 87 on pretest to 89.71 on posttest, accompanied by a decrease in standard deviation, showing a more consistent distribution of scores. N-gain analysis revealed that most students achieved medium to high improvement, especially those with lower initial pretest scores. Furthermore, the Effectiveness Index highlighted that several students experienced significant learning progress, demonstrating that History Quest effectively supports learners with diverse initial abilities. The novelty of this research lies in integrating visual search technology with Guided Inquiry Learning to create an engaging, interactive, and technology-based history learning experience.